One Company – Many Worlds. Activity Diversification within Business Entities: the Example of Dolnośląskie Voivodeship - Raczyk, Andrzej (Przedsiębiorczość - Edukacja, 2020)
One of the significant problems related to business entities is the implementation of a number of different types of activity by individual companies. This issue, despite being relatively well researched among individual or groups of businesses has yet to be studied comprehensively. This is due to the fact that the vast majority of studies focus only on the predominant type of activity declared at the time of company registration. The objective of this research was to identify regularities in the number and structure of activity types within individual business entities in Dolnośląskie Voivodeship. The survey covered all entities actively operating in the region - almost 176 000 in total. The study examined all types of activity carried out (according to PKD 2007 including the subclass level) as well as their location (by gmina). The research was based on data from the Central Register and Information on Economic Activity. The study showed that the population is dominated by those conducting many different activities - about 8.2 per company on average. The inclusion of all (and not just dominant) activities affects the observed economic structures, including the spatial dimension.